Tumor-Associated Macrophages: Critical Players in Drug Resistance of Breast Cancer - Xiao, Maoyu; He, Jun; Yin, Liyang; Chen, Xiguan; Zu, Xuyu; Shen, Yingying (Frontiers in Immunology, 2021)
Drug resistance is one of the most critical challenges in breast cancer (BC) treatment. The occurrence and development of drug resistance are closely related to the tumor immune microenvironment (TIME). Tumor-associated macrophages (TAMs), the most important immune cells in TIME, are essential for drug resistance in BC treatment. In this article, we summarize the effects of TAMs on the resistance of various drugs in endocrine therapy, chemotherapy, targeted therapy, and immunotherapy, and their underlying mechanisms. Based on the current overview of the key role of TAMs in drug resistance, we discuss the potential possibility for targeting TAMs to reduce drug resistance in BC treatment, By inhibiting the recruitment of TAMs, depleting the number of TAMs, regulating the polarization of TAMs and enhancing the phagocytosis of TAMs. Evidences in our review support it is important to develop novel therapeutic strategies to target TAMs in BC to overcome the treatment of resistance.